w4CSeq: software and web application to analyze 4C-seq data - Cai, Mingyang (Bioinformatics, 2016)
Summary: Circularized Chromosome Conformation Capture followed by deep sequencing (4C-Seq) is a powerful technique to identify genome-wide partners interacting with a pre-specified genomic locus. Here, we present a computational and statistical approach to analyze 4C-Seq data generated from both enzyme digestion and sonication fragmentation-based methods. We implemented a command line software tool and a web interface called w4CSeq, which takes in the raw 4C sequencing data (FASTQ files) as input, performs automated statistical analysis and presents results in a user-friendly manner. Besides providing users with the list of candidate interacting sites/regions, w4CSeq generates figures showing genome-wide distribution of interacting regions, and sketches the enrichment of key features such as TSSs, TTSs, CpG sites and DNA replication timing around 4C sites. Availability and Implementation: Users can establish their own web server by downloading source codes at https://github.com/WGLab/w4CSeq. Additionally, a demo web server is available at http://w4cseq.wglab.org. Contact: kaiwang@usc.edu or wangelu@usc.edu Supplementary information: Supplementary data are available at Bioinformatics online.